Gwendolyn Moore: The “Ordinary” Translator as Cultural Intermediary - Panofsky, Ruth (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
This essay draws on archival materials in the Harvest House fonds housed at Queen’s University (Kingston, Ontario) to recover and demystify the nature of Gwendolyn Moore’s formative work in French‑to‑English translation in the years 1970 to 1973. The essay responds to Jeremy Munday’s call to attend to the “ordinary” translator who did not gain prominence but whose work was nonetheless integral to the cultural fabric of her society. In focusing on Moore’s connection with Harvest House publisher Maynard Gertler and studying her role as the trailblazing translator of Yves Thériault and Anne Hébert, the essay argues that she became a key intermediary of cultural exchange in the early 1970s, when the Canadian government was yet in the process of formalizing a program of arts translation grants under the aegis of the Canada Council for the Arts. In essence, before translators had acquired professional standing within literary Canada, Moore conducted herself as a professional.